2019
DOI: 10.1098/rsif.2019.0028
|View full text |Cite
|
Sign up to set email alerts
|

Epicardial prestrained confinement and residual stresses: a newly observed heart ventricle confinement interface

Abstract: The heart epicardial layer, with elastin as the dominant component, has not been well investigated, specifically on how it contributes to ventricular biomechanics. In this study, we revealed and quantitatively assessed the overall status of prestraining and residual stresses exerted by the epicardial layer on the heart left ventricle (LV). During porcine heart wall dissection, we discovered that bi-layered LV surface strips, consisting of an epicardial layer and cardiac muscle, always curled towards th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 43 publications
1
14
0
Order By: Relevance
“…From the study of opening angle in an arterial ring, it is found that the presence of residual stress leads to a homogenous distribution of the circumferential wall stress through the vessel thickness [38]. For myocardium, Shi et al measured the residual stress by a curling angle characterization and found that the residual stress protected the ventricle wall by reducing myocardial stress during LV diastolic expansion [34]. The measurement of residual stress in myocardium is seldom seen in ex vivo mechanical tests and future experimental studies may consider to include such measurement.…”
Section: Preconditioning and Residual Stress Measurementmentioning
confidence: 99%
See 1 more Smart Citation
“…From the study of opening angle in an arterial ring, it is found that the presence of residual stress leads to a homogenous distribution of the circumferential wall stress through the vessel thickness [38]. For myocardium, Shi et al measured the residual stress by a curling angle characterization and found that the residual stress protected the ventricle wall by reducing myocardial stress during LV diastolic expansion [34]. The measurement of residual stress in myocardium is seldom seen in ex vivo mechanical tests and future experimental studies may consider to include such measurement.…”
Section: Preconditioning and Residual Stress Measurementmentioning
confidence: 99%
“…While the uniaxial mechanical test offers a quicker and easier examination of the material mechanical property, the biaxial mechanical test better mimics the in vivo loading conditions and provides more comprehensive measurements of the anisotropic mechanical behavior [ Residual stress is the stress that remains in the tissue after all external loads are removed [33]. The presence of residual stress in myocardium has been observed in both large animal (porcine) and small animal (rat) ventricles [34][35][36][37]. The exact cause of residual stress in biological tissues is not fully clear, but the different growth rates at different layers or directions of the tissue are likely the reason [36].…”
Section: Uniaxial and Biaxial Tensile Mechanical Testsmentioning
confidence: 99%
“…The myocardial extracellular matrix (ECM) plays a key role in defining the overall helical architecture of the heart, promoting active contraction by the cardiomyocytes within its network and ensuring appropriate passive stretch to prevent overstretching during diastole. However, recent scientific discoveries have implicated the elastin-rich epicardial layer as another key component in regulating cardiac mechanics [ 36 , 37 ].…”
Section: Cardiac Mechanostructurementioning
confidence: 99%
“…Recent studies have investigated the mechanical role of the epicardial layer [ 36 , 37 ]. The epicardial layer is under tension in vivo ; removal of this load by explant results in the recoil of the epicardium and subsequent bending of the ventricular tissue attached to it.…”
Section: Cardiac Mechanostructurementioning
confidence: 99%
“…The ECM within the myocardium is mostly Types I and III collagen, mixed with a sparse distribution of elastin fibers. The final structural component affecting overall heart function is the pericardial sac, a thin collagenous membrane encasing the ventricles, separated from them by a thin layer of fluid (Shi et al, ). One of the many challenges in designing cardiac patches is taking the important structural components into consideration for fabricating a material that will integrate well into the complex anatomy of the heart.…”
Section: Cardiac Tissue Microstructure and Composition And Cardiac Pamentioning
confidence: 99%